Exploring Register Variation in Korean Popular Music (K-Pop) - Aniuranti, Asfi (Universitas Ahmad Dahlan, 2019)
In sociolinguistics, language varieties are one of interesting topics discussed, and among those varieties, there is a variety called register. This study itself investigates one of register features namely English terms in Korean Popular Music (K-Pop). The topic is chosen due to the high number of English terms in K-Pop (at least 105 terms) and the difficulties in understanding their meanings. The objectives of this study are (1) describing the form of the terms, (2) describing the formation of the terms, and (3) explaining the specificity of the meanings by comparing the meanings of the terms with the meanings on the dictionary. This study was conducted through several phases called data gathering, data analysis and result presentation of data analysis. Overall, the results reveal several prominent findings. First, most of the terms are in a form of word, meanwhile the terms in phrase are limited. Second, there are several types of term manufacturing, and the most dominant one is compounding. Third, most of the terms’ meanings have been changed from meanings on the dictionary, and they are classified as semantic narrowing.